Counseling, Motivation of Midwives on IUD KB Acceptors, and Usage of IUD KB in Working Area of Dermayu Public Health Center Seluma District - Elza Wulandari; Santoso Ujang Effendi; Purwaningsih Purwaningsih (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
IUD contraception is a contraceptive that has a long period of time, is very effective and comfortable for nursing mothers, if released fertility will return soon. The purpose of this study was to study the relationship of counseling and motivation of midwives on IUD family planning acceptors with the use of IUD family planning in the working area of the Dermayu Public Health Center in Seluma District. The design used in this study is an analytical survey with a cross sectional approach. The population in this study were all active family planning participants from January to July 2018 in the work area of Dermayu Public Health Care Center which amounted to 813 people. The sample in this study amounted to 97 respondents. Taking techniques using Accidental Sampling techniques. Data collection uses primary data by distributing questionnaires to respondents. The results showed that 78.4% of mothers did not use IUD KB, 21.6% of mothers used IUD KB. 41.2% of mothers did not get counseling about family planning and 58.8% of mothers received good counseling. 71.1% of mothers have low motivation and 28.9% of mothers have high motivation. There is a significant relationship between counseling midwives on IUD KB acceptors with the use of IUD family planning in the working area of Dermayu Public Health Center in Seluma District with a weak category. There is a significant relationship between the motivation of midwives on IUD KB acceptors with the use of IUD family planning in the working area of Dermayu Public Health Center in Seluma District with the moderate category. It is expected that health workers can provide socialization and counseling to couples of childbearing age so that they can determine or choose appropriate long-term contraceptives. Keywords: counseling, motivation of midwives, usage of IUD